A Theoretical Study on the Structure, Intramolecular Interactions, and Detonation Performance of Hydrazinium Dinitramide. Issue 1 (23rd September 2013) - Zhang, Xueli; Liu, Yan; Wang, Fang; Gong, Xuedong
Abstract The structures of hydrazinium dinitramide (HDN) in the gas phase and in aqueous solution have been studied at different levels of theory by using quantum chemistry. The intramolecular hydrogen‐bond interactions in HDN were studied by employing the quantum theory of atoms in molecules (QTAIM), as well as those in ammonium dinitramide (ADN), hydrazinium nitroformate (HNF), and ammonium nitroformate (ANF) for comparison. The results showed that HDN possessed the strongest hydrogen bonds, with the largest hydrogen‐bond energy (−47.95 kJ mol−1) and the largest total hydrogen‐bond energy (−60.29 kJ mol−1). In addition, the charge transfer between the cation and the anion, the binding energy, the energy difference between the frontier orbitals, and the second‐order perturbation energy of HDN were all the largest among the investigated compounds. These strongest intramolecular interactions accounted for the highest decomposition temperature of HDN among all four compounds. The IR spectra in the gas phase and in aqueous solution were very different and showed the significant influence of the solvent. The UV spectrum showed the strongest absorption at about 253 nm. An orbital‐interaction diagram demonstrated that the transition of electrons mainly happened inside the anion of HDN. The detonation velocity (D=8.34 km s−1) and detonation pressure (P=30.18 GPa) of HDN were both higher than those of ADN (D=7.55 km s−1 and P=24.83 GPa). The composite explosive HDN/CL‐20 with the weight ratio wCL−20/wHDN=0.388:0.612 showed the best performance (D=9.36 km s−1, P=39.82 GPa), which was close to that of CL‐20 (D=9.73 km s−1, P=45.19 GPa) and slightly better than that of the composite explosive ADN/CL‐20 (wCL−20/wADN=0.298:0.702, D=9.34 km s−1, P=39.63 GPa).